Genetic structure of the population of wild-growing vines of the Utrish Nature Reserve - E. T. Ilnitskaya; M. V. Makarkina; I. V. Gorbunov; I. V. Stepanov; T. D. Kozina; E. A. Kozhevnikov; V. K. Kotlyar (Вавиловский журнал генетики и селекции)
Grapes are one of the most common agricultural crops in the world. Currently, the analysis of genotypes directly at the DNA level is considered to be the most accurate method for studying the plant gene pool. The study of wild vines and ancient varieties in various regions of viticulture is an important direction of research in this field. The purpose of this work was to study the population of wild grapes growing on the territory of the Utrish Nature Reserve on the Black Sea coast of Krasnodar Region. The territory of the reserve is of interest as it is a site of ancient settlements, and the environmental conditions are suitable for the growth of wild grapes. During the survey of the territory, 24 samples of wild grapes were found, which were described according to the main morphological characteristics and analyzed by the molecular genetic method. The found vines were genotyped using 15 DNA markers, including nine commonly used for DNA fingerprinting (VVS2, VVMD5, VVMD7, VVMD25, VVMD27, VVMD28, VVMD32, VrZAG62, VrZAG79) and VVIb23, which allows determining hermaphrodite and dioecious vines. Statistical processing of microsatellite loci polymorphism data was carried out using the GenAlEx 6.5 program. The genetic relationships of the studied vines were evaluated using the PAST 2.17c program. The samples were found to be morphologically and genetically polymorphic. The number of alleles identified in the sample varied from 5 to 18 and averaged 8 alleles per locus. Statistical processing of DNA analysis data made it possible to identify two genetically different populations among the wild discovered vines. An assessment of genetic similarity of the found vines with some local varieties of geographically close viticulture regions, rootstocks and representatives of Vitis sylvestris from other territories was made. One of the populations found in the Utrish Nature Reserve is close to a number of V. sylvestris genotypes, the DNA profiles of which are presented in the Vitis International Variety Catalogue.